Enhanced rehabilitation for unstable pelvic tile C fractures: integrating mechanotherapy and early intervention - Khan Akhtar Ali; LingXiao He; Weikai Zhang; Chengyan Xia; Hui Huang; Hui Huang Emails (Journal of Orthopaedic Surgery and Research)
Abstract Background and Objectives This study aimed to enhance the rehabilitation process for patients with unstable pelvic Tile C fractures resulting from polytrauma by integrating mechanotherapy using the Hocoma Lokomat robotic device with conventional rehabilitation methods. The goal was to improve functional recovery outcomes and minimize pain levels following surgical intervention. Methods A total of 74 participants, aged 21 to 65 years, with severe unstable pelvic Tile C fractures were enrolled at Tongji Hospital’s Department of Rehabilitation from 2022 to 2024. They were randomly divided into two groups: Group A (34 patients) received comprehensive rehabilitation including mechanotherapy with the Hocoma Lokomat, while Group B (40 patients) underwent only conventional therapeutic exercises. Functional outcomes were assessed using the Majeed pelvic score, and pain were monitored over time. Results Group A demonstrated significantly better pelvic function scores compared to Group B throughout the rehabilitation period(91.53 ± 4.10vs. 88.17 ± 5.15). Additionally, at the six-month follow-up, Group A showed superior pain control benefits attributed to mechanotherapy(2.09 ± 1.10vs2.29 ± 1.12). Conclusion Integrating the Hocoma Lokomat into rehab for unstable pelvic Tile C fractures improves function and pain control versus conventional care. The study supports robotic-assisted therapy’s benefits for polytrauma patients, advocating innovative rehab approaches.